Severe impact of late diagnosis of congenital adrenal hyperplasia on gender identity, sexual orientation and function: case report and review of the literature - Simeoli, Chiara; de Angelis, Cristina; Delli Veneri, Alessandra; Menafra, Davide; Di Paola, Nicola; Pivonello, Claudia; Di Somma, Carolina; Valerio, Paolo; Melis, Daniela; Alviggi, Carlo; Colao, Annamaria; Pivonello, Rosario (Frontiers in Genetics, 2022)
Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21-OHD) represents the most frequent form of CAH and of 46,XX disorder of sex development in female newborns. In the majority of cases, particularly in developed countries, female patients suffering from the classic forms of CAH reached the diagnosis at birth or in the early childhood, allowing a prompt treatment with a correct gender assignment. The current manuscript describes an unusual case of an Italian 46-year-old woman, homeborn in the 60s, receiving an extraordinarily late diagnosis of simple virilising classic form of CAH due to 21-OHD, determining a relevant impairment of both physical and psychosexual development. The patient presented primary amenorrhea, height under target, overweight with visceral adiposity, hypercholesterolemia and insulin resistance, hirsutism with a typical male-pattern hair growth, external genital ambiguity, and particularly, a severe impairment in the entire series of psychological dimensions, particularly severe depressive symptoms, together with gender dysphoria relative to the female gender assigned at birth, cross-gender behaviours, body image discomfort, homosexual orientation, and sexual dysfunction. Following diagnosis and glucocorticoid (GC) replacement therapy, the hyperandrogenism control and familial and socio-cultural factors changes, particularly, living alone and the interruption of social isolation, were accompanied by menarche appearance, improvement in hirsutism and metabolic profile, and a resolution in all psychological dimensions, depressive symptoms, and gender dysphoria. The patient began to perceive homosexual orientation without discomfort, breaking marginalization, and ameliorating sexual function. Few cases of female patients with CAH due to 21-OHD receiving an extremely delayed diagnosis have been published. However, to the best of our knowledge, this is the first case including a complete psychosexual assessment at diagnosis with a detailed re-evaluation after 5 years of disease treatment.